The correlation between dietary fat quality indices and lipid profile with Atherogenic index of plasma in obese and non-obese volunteers: a cross-sectional descriptive-analytic case-control study - Maryam Sadat Moussavi Javardi; Zahra Madani; Ariyo Movahedi; Majid Karandish; Behnood Abbasi (Lipids in Health and Disease, 2020)
Abstract Background and aim Abnormalities in lipid metabolism are commonly observed in patients who were obese. Alongside dyslipidemia, one of the markers in predicting the risk of cardiovascular disease is the Atherogenic Index of Plasma (AIP), which is related to dietary intake. Healthy fat quality indices might affect on AIP. The purpose of this study is to find the possible relationship between dietary fat quality, and AIP and comparison of these indices among obese and non-obese volunteers. Methods This study was a cross-sectional descriptive-analytic case-control study with 157 normal and overweight and obese volunteers (n = 71 normal, Age: 38.90 ± 10.976 vs n = 86 overweight/obese, Age: 38.60 ± 9.394) in the age range of 18–65 years. Food intake was measured using FFQ, anthropometric indices (weight, height, body mass index and waist to hip ratio), body composition (visceral fat level, total body water, body fat mass), and lipid profile were measured. Results Based on the present results, comparable biochemical parameters including TC (P = 0.580), TG (P = 0.362), LDL (P = 0.687) and HDL (P = 0.151) among overweight/obese volunteers as compared to normal ones were noticed. Effects of dietary fat quality, including Atherogenicity (AI) and Thrombogenicity (TI) hypo/hypercholesterolemic ratio (h/H), the Cholesterol-Saturated Fat Index (CSI) showed significantly higher AI (P = 0.012) in the overweight/obese group as compared to the normal group. Whereas, h/H (P = 0.034) and ω-6/ω-3 ratio (P = 0.004) were significantly higher in normal-weight volunteers. There was a positive correlation between AI, TI, CSI, SFA, MUFA, PUFA and ω-6/ω-3 ratio with AIP and negative correlation between h/H with AIP in both groups. Despite the significances of these correlations no strong relation was observed by doing multiple regression among normal and overweight/obese groups (R 2 = 0.210, R 2 = 0.387). Conclusions In summary, the present work proposes a direct relationship between dietary fat quality, increased BMI, and lipid abnormalities with AIP. Nevertheless, further large-scale studies are required to sustain a clear conclusion in this wish.